ENDOMETRIAL HISTOPATHOLOGICAL PATTERNS IN PATIENTS WITH ABNORMAL UTERINE BLEEDING: A SIX MONTHS OBSERVATION OF 285 CASES IN A TERTIORY CARE HOSPITAL - ABHILASHA; GUNJA DWIVEDI; ASHISH; NAVED KHAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: the objective of the study was to assess the histopathological patterns of endometrial lesions in patients with abnormal uterine bleeding (AUB) across different age groups. Methods: A descriptive cross-sectional study was conducted over 6 months at RNT Medical College, Udaipur after the approval of the Institutional Ethics Committee. A total of 285 cases presenting with AUB were analyzed through clinical history, physical examination, and endometrial biopsy. Cases were categorized into reproductive, perimenopausal, and postmenopausal groups for comparative analysis. Results: The perimenopausal group had the highest incidence of AUB (50.88%). The most common histopathological findings included secretory (39%) and proliferative (31%) phases. Senile cystic atrophy was prevalent in postmenopausal women (38.71%), while endometrial hyperplasia was observed more in perimenopausal and postmenopausal women. Malignant cases, including adenocarcinoma, were rare but significant, particularly in the postmenopausal group. Conclusion: Age-specific variations in endometrial patterns highlight the influence of hormonal changes and the increased risk of malignancy in postmenopausal women. The findings support the importance of endometrial histopathological evaluation in managing AUB, especially in perimenopausal and postmenopausal patients to identify potentially precancerous conditions.